Kualitas Sungai Bilah Berdasarkan Biodiversitas Fitoplankton Kabupaten Labuhanbatu, Sumatera Utara - Rivo Hasper Dimenta; Riska Agustina; Rusdi Machrizal; Khairul Khairul (Universitas Hasanuddin, 2020)
Phytoplankton is the most important organism for aquatic ecosystem life that make up organic substances from inorganic substances in the process of photosynthesis and the largest oxygen producer for the life of living creatures. Research on the diversity of phytoplankton in river blades has never been done . The purpose of this study is to determine the biodiversity of phytoplankton in Bilah river and analyze the relationship of physical-chemical factors of the water to the diversity of phytoplankton. The study was conducted from April to June 2019. This research is an exploratory descriptive study with the selection of sampling locations using purposive sampling method. Analysis of data includes density of phytoplankton, measurement of physical-chemical factor of aquatic biology and the Correlation analysis between phytoplankton and value of physical-chemical factor. The results showed Nostoc sp.were the highest density of phytoplankton found on the first (1st) station, while the lowest abundance value is found on stations 2nd and 3rd were found genus Rhizosolenia sp. and Euglena sp. The Highest Shanon-Wiener index (H’) value on the first (1st) station (2.26) dan the lowest value on stasiun 3rd (1.24). The summary from this research were DO, temperature, and light intensity as physical factor of water had the highest correlation againts of biodiversity of phytoplanton.